Estudio sobre el muestreo de la puesta invernal del acaro rojo Panonychus ulmi (Koch) en ramas de manzano - Costa-Comelles, J.=700 1 Vercher, R.; Soto, A.
(En, Es)
ilus., 10 ref.
Keywords: ACARINA; MANZANA; PANONYCHUS; MUESTREO; OVULO; INVIERNO; ESPAÑA